EFEKTIVITAS KONSELING TEMAN SEBAYA (PEER COUNSELING) DALAM MEREDUKSI BURNOUT AKADEMIK KELAS XI SMAN 1 PAGERBARANG - Riani, Wina; Adicita, Rizal; Atmaja, Jati Rinakri (Jurnal Muria Research Guidance and Counseling (MRGC), 2024)
This research was motivated by the phenomenon of academic burnout which is often experienced by students which is shown by lazy behavior in studying and being sleepy during teaching and learning activities. The aim of this research is to determine the level of academic burnout and the effectiveness of peer counseling in reducing academic burnout in class XI at SMAN 1 Pagerbarang. The method used is experimental research with a one group pretest posttest design. The research results show that (1) the level of academic burnout is in the medium category with a score of 369; (2) peer counseling can reduce academic burnout as indicated by a sig score. 0.0000.05 and a decrease in pretest and posttest scores of 38,635 to 26,625; (3) peer counseling is quite effective in reducing academic burnout as seen from the N Gain score of 56%